Partially encased columns: strenght and stiffness effect on the buckling resistance under fire - Piloto, P.A.G. (2018)
Partially encased columns are made of composite steel and concrete between flanges. The temperature field and time evolution in each material is required to determine the fire resistance. The annex G of the Eurocode 4 part 1- 2, presents a simplified calculation method, using the balanced summation model for the calculation of the plastic resistance to axial compression and the effective flexural stiffness. Previous studies revealed unsafe results when using the annex G of the Eurocode 4. New proposals are being developed for the calculation of the strength and stiffness for the four components (flanges, web, concrete and reinforcing bars). New improvements are proposed for the balanced summation model, based on the nonlinear thermal numerical solution method, presenting safer values.